Clinical and Immunological Parameters of Newcastle Disease Vaccination in Juvenile Ring - Necked Pheasants (Phasianus colchicus) - Schmidt, Elizabeth Moreira Dos Santos; Paulillo, Antonio Carlos; Caron, Luiz Felipe; Filho, Tobias Fernandes; Agustini, Marcelo; Ventura, Henrique Larsen Brunow; Junior, Luciano Doretto (International Journal of Poultry Science, 2008)
Clinical and immunological parameters of vaccinated ring-necked pheasants against Newcastle disease were evaluated. Sixty young birds were distributed into four different experimental groups, vaccinated or not against Newcastle disease (ND): G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain) and G4 (nonvaccinated -control). The immune response was evaluated by the HI test. The vaccinations of pheasants with NDV Ulster 2C, B1 and LaSota strains did not cause any clinical signs associated with post-vaccinal reactions and were similar in the humoral immune response stimulus (HI).